2017
DOI: 10.1007/s11746-017-3008-9
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Profile, Color and Antioxidant Capacity of Arbequina Virgin Olive Oils from Different Irrigation Treatments

Abstract: Olive fruits and virgin olive oils from a super‐high‐density olive orchard cv. Arbequina under different irrigation treatments (Control, RDI1, RDI2) were characterized by their pigment profile, CIElab colorimetric coordinates, oxidative stability and antioxidant capacity during the olive seasons 2011 and 2012. The control treatment were irrigated according to the total evapotranspiration of the olive grove (100% ETc), while RDI1 and RDI2 consisted of moderate and severe deficit irrigation, respectively. Olive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…However, previous works on the effects of irrigation on the carotenoid content found different responses. Sena-Moreno et al [59] reported an increase in carotenoids with water restriction, consistent with our results, while Tovar et al [18] did not find differences. The content in Arbequina was reduced by 65% (2019) and 81% (2021) in the non-irrigated treatment compared to the irrigated ones.…”
Section: Discussionsupporting
confidence: 92%
“…However, previous works on the effects of irrigation on the carotenoid content found different responses. Sena-Moreno et al [59] reported an increase in carotenoids with water restriction, consistent with our results, while Tovar et al [18] did not find differences. The content in Arbequina was reduced by 65% (2019) and 81% (2021) in the non-irrigated treatment compared to the irrigated ones.…”
Section: Discussionsupporting
confidence: 92%
“…(2009) (Gómez- Rico et al 2009) also presented higher values of these parameters in EVOO following water stress treatment Sena-Moreno et al (2017) (Sena-Moreno et al 2017. …”
mentioning
confidence: 88%
“…[40][41][42] Table olives with too much or too little water produce less phenolic compounds than when RDI is performed, which is a method that causes the fruit to develop. Other investigations have shown that an RDI method can boost antioxidant activity by inducing mild drought stress 21 and phenolic content in olive paste, especially oleuropein, hydroxytyrosol, tyrosol and verbascoside. 21 The results showed that the irrigation strategy for 'Arbequina' and 'Koroneiki' neither promoted nor inhibited acrylamide formation when processed industrially.…”
Section: Rdi Versus Full Irrigation Strategiesmentioning
confidence: 99%
“…Other investigations have shown that an RDI method can boost antioxidant activity by inducing mild drought stress 21 and phenolic content in olive paste, especially oleuropein, hydroxytyrosol, tyrosol and verbascoside. 21 The results showed that the irrigation strategy for 'Arbequina' and 'Koroneiki' neither promoted nor inhibited acrylamide formation when processed industrially. No literature references were found of statistical interactions between irrigation and elaboration style.…”
Section: Rdi Versus Full Irrigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation